Silicon carbide crystal and method for producing same

By introducing aluminum dopants into the silicon carbide crystal, the optical absorption problem caused by boron and nitrogen impurities is solved, and the light absorption coefficient and optical transparency are reduced in the visible light range are achieved.

CN119800507APending Publication Date: 2025-04-11II VI DELAWARE INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411915070.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-09-23
Filing Date
2021-03-01
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing silicon carbide crystals have optical absorption limitations in optical applications, mainly due to near-band edge absorption caused by boron and nitrogen impurities, and it is challenging to reduce impurities through physical gas phase transfer technology.

Method used

By introducing an aluminum dopant into the silicon carbide crystal, the concentration of aluminum exceeds the combined concentration of residual boron and nitrogen impurities, and the concentration of aluminum dopant is controlled during growth to reduce light absorption.

Benefits of technology

It effectively reduces the light absorption coefficient of silicon carbide crystals in the visible light range, improves optical transparency, and makes it more suitable for applications such as optical windows, lenses and optical waveguides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800507A_ABST
    Figure CN119800507A_ABST
Patent Text Reader

Abstract

The present disclosure relates generally to silicon carbide crystals that can be used in optical applications, and to methods for producing the same. In one form, the composition comprises aluminum doped silicon carbide crystals, the aluminum doped silicon carbide crystals having residual nitrogen and boron impurities. A concentration of aluminum in the silicon carbide crystal is greater than a combined concentration of nitrogen and boron in the silicon carbide crystal, and the silicon carbide crystal has a light absorption coefficient of less than about 0.4 cm-1 at a wavelength in the range of about 400 nm to about 800 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of March 1, 2021, application number 202110237647.6, and invention name “Silicon carbide crystal and method for producing the same”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to U.S. Provisional Patent Application No. 62 / 984,177, filed on March 2, 2020, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0004] The present disclosure relates generally to silicon carbide crystals and methods for producing the same. More particularly, but not exclusively, the present disclosure relates to silicon carbide crystals that may be suitable for use in optical applications and to methods for producing the same. Background Art

[0005] Unless otherwise indicated herein, the materials described herein are not prior art to the claims in this application and are not admitted to be prior art by inclusion in this section.

[0006] Large, industrial-sized silicon carbide (SiC) single crystals can be grown from the vapor phase by a sublimation technique commonly referred to as physical vapor transport (PVT). In this technique, a silicon carbide source, which may be in the form of silicon-carbon powder or grains, may be provided in a high temperature region of a crucible. A silicon carbide seed, such as a single crystal silicon carbide plate or wafer of a 4H or 6H polytype, may be positioned in a lower temperature region of the crucible. The crucible may be heated to sublime the silicon carbide source and fill the crucible with the gaseous products of the sublimation. The resulting vapor migrates to the cooler silicon carbide seed and deposits on the seed to grow a silicon carbide crystal boule of the desired polytype, diameter, and thickness.

[0007] During sublimation growth, the silicon carbide crystal may be exposed to various impurities present in the growth system, and such exposure may result in the formation of an impurity background in the crystal. Background impurities found in silicon carbide crystals include boron and nitrogen, which may be present in concentrations as high as n·10 16 cm -3 In silicon carbide crystals grown by sublimation, graphite can be a source of boron and nitrogen background impurities.

[0008] The optical properties of bulk silicon carbide single crystals grown by sublimation have been studied, and the overall optical absorption properties of pure, undoped or otherwise unintentionally doped hexagonal silicon carbide crystals are described in Singh et al., "Nonlinear optical properties of hexagonal silicon carbide", Appl. Phys. Lett, Vol. 19, 2 (1971) 53-56. The description shows that the substantially transparent region of silicon carbide crystals of this nature extends from the band edge cutoff (about 380 nm for 4H and about 410 nm for 6H) to λ≈4 μm in the infrared, where it terminates with a multiphonon absorption band. The size of the near-band edge absorption shoulder is about 1 cm -1 , which is typical for undoped 4H-SiC and 6H-SiC crystals.

[0009] Sublimation-grown SiC heavily doped with boron, nitrogen, and aluminum up to 10 18 cm -3 Optical properties of 4H and 6H silicon carbide single crystals of or higher. Each of these impurities produces a specific near-band edge absorption band in the visible light range. The light absorption band peak associated with boron is at about 430nm to 480nm for 4H-SiC and at about 450nm to 510nm for 6H-SiC. The absorption shoulder associated with aluminum is at about 410nm to 420nm and is very close to the band edge cutoff. The absorption band associated with nitrogen is at about 460nm to 470nm in 4H and at about 620nm to 630nm in 6H.

[0010] Although some optical transparency has been observed in these crystals, their optical applications have been found to be very limited, primarily due to optical absorption that may be caused by residual impurities. One way to minimize near-band edge absorption in sublimation-grown 4H and 6H polytype SiC crystals is to reduce the presence of unwanted background impurities. However, given the high temperatures of the PVT growth process and the use of graphite as the crucible material, reducing the boron and nitrogen background impurities in PVT-grown SiC single crystals to less than 1·10 15 cm -3 The level can be considered at least challenging, even if unrealistic.

[0011] Therefore, additional contributions to this technology are still needed.

[0012] The subject matter claimed herein is not limited to implementations that solve any disadvantages or that operate only in environments such as those described above. Rather, this background is merely provided to illustrate one exemplary technology area in which some implementations described herein may be implemented. Summary of the invention

[0013] This Summary is provided to introduce a selection of concepts in a simplified form that are further described below in the Detailed Description. This Summary is neither intended to identify key features or essential characteristics of the claimed subject matter nor is it intended to be used as an aid in determining the scope of the claimed subject matter.

[0014] In one embodiment, the composition comprises an aluminum-doped silicon carbide crystal having residual nitrogen and boron impurities. The silicon carbide crystal comprises aluminum in the silicon carbide crystal at a concentration greater than the combined concentration of nitrogen and boron in the silicon carbide crystal, and the silicon carbide crystal has a light absorption coefficient of less than about 0.4 cm at a wavelength in a range of about 400 nm to about 800 nm. -1 .

[0015] In another embodiment, a method for preparing an aluminum-doped silicon carbide crystal includes providing a silicon carbide source material and a silicon carbide single crystal seed in a growth crucible. The method also includes providing a solid aluminum dopant source material containing a compound containing aluminum and oxygen in a container. The growth crucible is heated in the following manner when the container is positioned in the growth crucible, the manner being effective in generating a silicon- and carbon-containing vapor from the silicon carbide source material in the growth crucible and generating an aluminum-containing vapor from the solid aluminum dopant source material in the container, and being effective in depositing the silicon- and carbon-containing vapor and the aluminum-containing vapor on the silicon carbide single crystal seed to grow an aluminum-doped silicon carbide crystal. The container comprises a first material that resists damage to the aluminum dopant source and the aluminum-containing vapor, and a second material that resists damage to the silicon- and carbon-containing vapor.

[0016] Additional features and advantages of the present invention will be set forth in the following description, and in part will become apparent from the description, or may be learned through the practice of the present invention. Features and advantages of the present invention may be realized and obtained through the means and combinations particularly pointed out in the appended claims. These and other features of the present invention will become more fully apparent from the following description and the appended claims, or may be learned through the practice of the present invention set forth below. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to further illustrate the above and other advantages and features of the present invention, the present invention will be described in more detail by reference to specific embodiments of the present invention shown in the accompanying drawings. It should be understood that these drawings only depict typical embodiments of the present invention and should not be considered as limiting the scope thereof. The present invention will be described and explained with additional specificity and detail through the use of the accompanying drawings, in which:

[0018] Figure 1 is a schematic diagram of a system for sublimation growth of aluminum-doped silicon carbide crystals;

[0019] Figure 2 is used for Figure 1 A schematic diagram of a doping container in a system;

[0020] Figure 3 is the light absorption (α, cm) measured on 4H-SiC wafer -1 ) is a schematic diagram of the wavelength dispersion of ; and

[0021] Figure 4 is the light absorption (α, cm) measured on 6H-SiC wafer -1 ) is a schematic diagram of the wavelength dispersion of . DETAILED DESCRIPTION

[0022] Various aspects of exemplary embodiments of the present invention will now be described with reference to the accompanying drawings. It should be understood that the drawings are diagrammatic and schematic representations of such exemplary embodiments and are not limiting of the present invention, nor are they necessarily drawn to scale.

[0023] The present disclosure generally relates to silicon carbide crystals and methods for producing the same. More specifically, but not exclusively, the present disclosure relates to silicon carbide crystals that may be suitable for optical applications and methods for producing the same. Although various embodiments may be described in the context of use in optical components such as optical windows, lenses, and optical waveguides, for example, the embodiments disclosed herein may be employed in other fields or operating environments in which the functions disclosed herein may be useful. Therefore, the scope of the present invention should not be interpreted as being limited to the exemplary embodiments and operating environments disclosed herein.

[0024] The silicon carbide crystal disclosed herein can be a single crystal of a 4H or 6H polytype. In one form, the silicon carbide crystal can have high optical transparency in the visible spectrum. Silicon carbide crystals exhibiting these characteristics or similar characteristics can be used in various optical applications, such as, but not limited to, optical windows, lenses, and optical waveguides operating at wavelengths of about 410nm to about 750nm. Sublimation physical vapor transmission (PVT) technology can be used to grow optically transparent 4H and 6H silicon carbide crystals. In one form, the silicon carbide single crystal is doped with aluminum and contains residual boron and nitrogen impurities. On the one hand, the aluminum dopant exists in a concentration exceeding the combined concentration of residual nitrogen and boron impurities, otherwise it is below a level that may cause unstable crystal growth. Although it is not intended to be bound by any particular theory, it is believed that the aluminum dopant reduces the size of the near-band edge light absorption related to the presence of boron and nitrogen impurities. Similarly, keeping the lowest possible concentration of background boron and nitrogen impurities can also reduce light absorption.

[0025] As described above, sublimation techniques can be used to grow silicon carbide single crystals, including silicon carbide single crystals of 4H and 6H polytypes. On the one hand, these techniques can be designed to reduce or remove boron and nitrogen impurities in or from the growth system. For example, the presence of background boron can be reduced by using halogen-purified graphite parts (including but not limited to growth crucibles). In one form, the halogen purification of graphite parts can include heating graphite parts in a furnace chamber with an atmosphere containing chlorine, fluorine, or both chlorine and fluorine. At high temperatures, the carbon-bound boron present in graphite reacts with gaseous halogens such as chlorine and fluorine and forms volatile halides such as BCl3 and BF3. The volatile halides can be removed from the furnace chamber by an inert gas flow through the furnace chamber. After the purification, the graphite parts may still contain residual boron at a concentration of about 10 ppb by weight to about 100 ppb by weight. Similarly, silicon carbide crystals grown by sublimation of these purified graphite parts may still contain about 10 15 cm -3 Up to 10 16 cm -3 The concentration of residual boron impurities.

[0026] Reducing or removing nitrogen impurities in or from the growth system may include performing a pre-growth high temperature bake of the crystal growth hot zone in a vacuum. Alternatively, sublimation crystal growth may be performed under a flow of ultra-high purity argon. Silicon carbide crystals grown under these conditions may still contain a concentration of about 10 15 cm -3 Up to 10 16 cm -3 of residual nitrogen impurities.

[0027] Considering that even if steps are taken to reduce or remove impurities, some residual boron and nitrogen impurities may still remain, near-band edge light absorption may still exist due to their presence. However, as described above, the addition of aluminum dopants can be used to reduce the near-band edge light absorption caused by the presence of boron and nitrogen impurities. Similar to boron, aluminum is a shallow acceptor in 4H-SiC and 6H-SiC. In the SiC gap, the energy level of aluminum is located at about 0.2eV above the valence band maximum (see, for example, Atabaev et al., "Spectral Dependence of Optical Absorption of 4H-SiC Doped with Boron and Aluminum", J. of Spectroscopy (2018) Article ID 8705658 and online NSM Archive-Silicon Carbide (SiC)-Impurities and Defects). The lowest energy level of the boron acceptor is about 0.35eV above the valence band edge and is higher than the energy level of aluminum. As an acceptor, aluminum can be combined with boron that compensates for nitrogen (donor). If aluminum is introduced in sufficient concentration to make N Al +N B >N N , then all electrons are stripped from the nitrogen energy levels and thus no electrons are present at the bottom of the conduction band. Thus, nitrogen-related light absorption can be reduced or eliminated.

[0028] Doping with aluminum causes a redistribution of charge in the SiC crystal, which is reflected by a shift in the Fermi level position closer to the aluminum level. Al >N B +N N , then the Fermi level will move to a position lower than the lowest energy level of boron, thereby reducing or eliminating the electron population present at the boron energy level. Therefore, the light absorption associated with boron can be reduced or eliminated.

[0029] Considering the above, in order to “reduce” both the boron acceptor and the nitrogen donor from electrons, as shown in Equation (1), the concentration of the aluminum dopant (N Al ) exceeds the residual boron (N B ) and nitrogen (N N ) combined concentration:

[0030] N Al >N B +N N (1)

[0031] Doping with aluminum may result in aluminum-related light absorption, but any such absorption band will be very close to the band edge cutoff and will actually merge with it.

[0032] In aluminum-doped 4H and 6H silicon carbide polytypes, aluminum replaces silicon. The covalent radius of aluminum is The covalent radius of silicon is Considering the large radius of aluminum, the dissolution of aluminum in the silicon carbide crystal may cause local expansion and stress in the crystal lattice. At a certain concentration of aluminum, the formation of crystal defects, improperly oriented grains, and foreign polytypes may occur during the growth of the silicon carbide crystal. By keeping the concentration of aluminum below a certain level (e.g., about 5·10 17 cm -3 ) can avoid these problems, although variations are possible.

[0033] Although aluminum-doped silicon carbide single crystals can be grown by adding aluminum carbide (Al4C3) directly to a silicon carbide solid source, Al4C3 is unstable at high temperatures and may undergo decomposition into solid carbon and Al+C liquid through a peritectic reaction, where the partial pressure of gaseous aluminum over the liquid exceeds 100 Torr. Therefore, there may be an initial peak in aluminum concentration in the crystal followed by rapid consumption of the aluminum source.

[0034] U.S. Patent No. 8,216,369, the contents of which are incorporated herein by reference in their entirety, relates to more spatially uniform doping in a PVT process. For example, it discloses a growth method that includes a doping slow-release container loaded with a dopant and contained within a growth crucible. Figure 1 , schematically illustrates a system 10 for sublimation growth of aluminum-doped silicon carbide crystals having a more spatially uniform aluminum concentration throughout the crystal. System 10 includes a chamber 12 in which a growth crucible 14 is positioned. Crucible 14 is sealed by a lid 16 and surrounded by thermal insulation 18. Heating elements 20 are positioned about chamber 12 and are configured to provide heat to crucible 14. Heating elements 20 may be RF coils or resistive heating elements, although other variations are possible.

[0035] Within the crucible 14, a SiC source 22 and a SiC seed crystal 24 are arranged in a spatial relationship suitable for PVT crystal growth. More specifically, the SiC seed crystal 24 can be positioned near the top of the crucible 14 and can be, for example, attached or coupled to the lid 16, and the SiC source 22 can be positioned below the SiC seed crystal 24. The SiC source 22 is contained in a crucible 26 supported by a support structure 28. The support structure 28 includes a first member 30 spaced apart from a second member 32, and the first member 30 and the second member 32 extend from the lower portion of the crucible 14 toward the lid 16. In this arrangement, the crucible 26 and thus the SiC source 22 positioned in the crucible 26 are positioned above the lower portion of the crucible 14 with a free space 34 positioned therebetween. The first member 30 includes a hole 36 and the second member 32 includes a hole 38. The hole 36 and the hole 38 provide fluid communication between the free space 34 and a space positioned between the crucible 26 and the crucible 14, as shown in FIG. Figure 1 The direction is indicated by arrow A.

[0036] When the crucible 14 is heated by the heating element 20 during the sublimation growth of the crystal, the SiC source 22 vaporizes and fills the interior of the crucible 14 with a Si-containing and C-containing vapor that flows toward the SiC seed crystal 24 as shown by the directional arrow B. The Si-containing and C-containing vapor may contain volatile molecular species, such as Si, Si2C, and SiC2. A vertical temperature gradient may be established throughout the crucible 14, wherein the temperature of the lower portion of the crucible 14 is higher than the temperature of the upper portion of the crucible 14 (e.g., near the lid 16). A vertical temperature gradient of this nature creates a driving force for vapor transport as shown by the directional arrow B. The vapor transport brings vapor nutrients from the SiC source 22 to the SiC seed crystal 24. After reaching the SiC seed crystal 24, the supersaturated vapor is deposited on the SiC seed crystal 24, thereby causing the growth of a SiC single crystal 40 on the SiC seed crystal 24.

[0037] A slow-release doping container 42 that can be used for aluminum doping is positioned in the free space 34 in the crucible 14. The doping container 42 includes an internal space or chamber for receiving and holding a dopant source 44. In one form, the dopant source 44 is an aluminum dopant source and can be in the form of a solid aluminum compound having a low decomposition pressure at the SiC sublimation growth temperature. For example, in one form, the decomposition pressure can be less than about 1 Torr, although other variations are also possible. Non-limiting examples of solid aluminum compounds that can be used include oxygen-containing aluminum compounds, such as but not limited to aluminum carbonate, aluminum silicate, and aluminum oxide. In a specific but non-limiting form, the solid aluminum compound is aluminum oxide (Al2O3), which is also referred to as aluminum oxide. The aluminum oxide can be provided in the form of a pre-melted aluminum oxide "crack", such as a pure, undoped sapphire sheet. In general, the amount of dopant source 44 contained in the doping container 42 can be sufficient to support aluminum doping throughout the entire crystal growth cycle.

[0038] During the crystal growth cycle, the crucible 14 is heated and as the temperature of the crucible 14 increases to as high as about 2000°C, the oxygen-containing aluminum compound undergoes a chemical transformation that ultimately produces solid aluminum oxide. As the temperature of the crucible 14 further increases and reaches and exceeds the melting point of aluminum oxide of about 2040°C, the aluminum oxide melts and fills the interior of the doping vessel 42 with a vapor that is a product of evaporation and decomposition of the aluminum oxide melt. The vapor may contain molecules of Al2O3, Al2O, AlO, Al, and O. At the melting point of aluminum oxide, the total vapor pressure above the melt is about 0.01 Torr, while at 2200°C, it is less than 0.1 Torr. Similarly, if the temperature of the SiC sublimation growth process does not exceed about 2400°C, the vapor pressure of the molten aluminum oxide should not exceed about 1 Torr.

[0039] The doping vessel 42 includes a capillary channel, further details of which will be described below in conjunction with Figure 2 As discussed, the vapor containing aluminum and oxygen escapes from the doping vessel 42 through the capillary passage and migrates within the crucible 14, as shown in FIG. Figure 1 As shown by the direction arrow C in FIG. During the migration process, these vapors can contact and react with the carbon of graphite to form elemental aluminum vapor and carbon monoxide gas. Eventually, the aluminum vapor can reach the silicon carbide crystal growth interface and adsorb on the interface, thereby causing aluminum to dope the growing silicon carbide crystal.

[0040] Doping vessel 42 may be formed of one or more materials that provide stability in the high temperature environment of silicon carbide sublimation growth and resistance to attack by molten alumina and highly corrosive silicon and carbon containing vapors. Figure 2 In one non-limiting form, doping vessel 42 is formed of an outer component 46 and an inner component 48, with outer component 46 formed or positioned on or around inner component 48. Outer component 46 may be at least partially formed of a first material, and inner component 48 may be at least partially formed of a second, different material.

[0041] exist Figure 2In the form shown, the external component 46 is in the form of a crucible 50 including a lid 52. Since the crucible 50 and the lid 52 can be positioned in the free space 34 and thus can be exposed to the silicon- and carbon-containing vapor released by the SiC source 22, the crucible 50 and its lid 52 can be at least partially formed of a material that is corrosion-stable to the silicon- and carbon-containing vapor that may be present in the crucible 14. For example, at least the outer surface that may be in contact with the silicon- and carbon-containing vapor can be formed of a material that is corrosion-stable to the silicon- and carbon-containing vapor. Non-limiting examples of materials that can provide stability of this nature include graphite, carbides of refractory metals such as tantalum carbide (TaC) or niobium carbide (NbC), and graphite coated or layered with refractory carbides. In a specific but non-limiting form, the crucible 50 and its lid 52 can be formed of dense fine-grained graphite.

[0042] exist Figure 2 In the illustrated form, the internal assembly 48 is in the form of a crucible 54 including a lid 56. For example, the lid 52 of the crucible 50 may be removed to facilitate positioning of the crucible 54 and its lid 56 in the crucible 50, and the lid 52 may be reengaged with the crucible 50 to secure the crucible 54 and the lid 56 in the crucible 50. Because the crucible 54 and the lid 56 include an interior space or chamber for receiving and holding the dopant source 44 (which may be an aluminum dopant source, for example), and in turn may be exposed to molten aluminum oxide and to aluminum-containing vapors released by the dopant source 44, the crucible 54 and its lid 56 may be at least partially formed of a material that is stable to or resistant to corrosion or damage by the molten aluminum oxide or the aluminum-containing vapors. For example, at least the inner surfaces of the crucible 54 and the lid 56 that are disposed toward the dopant source 44 may be formed of a material that is stable to or resistant to corrosion or damage by the molten aluminum oxide or the aluminum-containing vapors. Non-limiting examples of materials that can provide stability of this nature include refractory metals or metal alloys such as, but not limited to, tantalum, molybdenum, tungsten, rhenium, or alloys thereof. In one specific but non-limiting form, crucible 54 and its lid 56 can be formed of tungsten.

[0043] Although the doping vessel 42 has been described as being formed of separate inner and outer components formed of different materials, it should be understood that the doping vessel 42 may also be made of a single component having a composite structure formed of different materials. For example, the different materials may be present in separate layers, where one layer of a first material is deposited on a second layer formed of a separate material. For example, in the case of the crucible 54 and the lid 56, these components may be formed of a first material and then a second material may be coated or affixed to their outer surfaces to provide a composite structure with the crucible 54 and the lid 56. Figure 2 The structure shown is similar to the structure shown, although other variations are possible.

[0044] As described above, the doping vessel 42 includes a capillary passage 58 through which a vapor containing aluminum and oxygen escapes from the doping vessel 42 when the aluminum oxide melts. The capillary passage 58 is formed by a hole 60 through the lid 52 and a hole 62 through the lid 56. The rate at which the vapor containing aluminum and oxygen can escape or be released from the doping vessel 42 can be controlled at least in part by the temperature at which the aluminum oxide melts and the size of the holes 60 and 62. For example, when the temperature at which the molten aluminum oxide is maintained is higher and the size of the holes 60 and 62 is larger, a higher rate at which the vapor containing aluminum and oxygen escapes or is released from the doping vessel 42 can occur. In some forms, the size of the holes 60 and 62 can be the same or different, with one or both having a diameter in the range of about 0.1 mm to about 1.5 mm.

[0045] The use of doping vessel 42 can, for example, facilitate the production of sublimation-grown silicon carbide single crystals containing a spatially uniform concentration of aluminum dopant throughout the crystal. The above techniques can also similarly avoid the situation where a high aluminum concentration is present in the first grown pear-shaped crystal portion of the crystal followed by rapid consumption of the aluminum source. In addition, the aluminum dopant concentration can be controlled so that it exceeds the combined concentration of residual boron and nitrogen while remaining below a level that causes crystal defects (e.g., about 5.10 17 cm -3 ).

[0046] Example

[0047] The following examples are provided for illustrative purposes and are not to be construed as limiting the invention disclosed in this document to only the embodiments disclosed in these examples.

[0048] Example 1

[0049] Four aluminum-doped SiC single crystals, two 4H polytypes and two 6H polytypes, were grown by sublimation. For comparison purposes, two additional SiC pear-shaped crystals, one 4H polytype and one 6H polytype, were grown by sublimation without aluminum doping. The experimental conditions for sublimation growth disclosed below are provided with reference to the above-described system 10.

[0050] Prepare similar to Figure 2The doping container 42 of the doping container. The doping container includes an inner crucible and a lid corresponding to or similar to the crucible 54 and the lid 56, made of pure tungsten available from Plansee USA LLC, 115 Constitution Boulevard, Franklin, MA 02038. The inner crucible has the following dimensions: 25 mm OD×15 mm ID×25 mm high. The lid is 5 mm thick and has a single through hole of 1.0 mm diameter drilled in its center. The outer crucible and lid corresponding to the crucible 50 and the lid 52 are made of halogen-purified dense isostatic graphite grade IG-11 available from Toyo Tanso USA Inc., 2575 NW Graham Cir, Troutdale, OR 97060. The outer crucible has the following dimensions: 32 mm OD×25 mm ID×30 mm high. The graphite lid is 5 mm thick and has a 1.0 mm diameter hole drilled in its center. The inner crucible fits tightly inside the outer graphite crucible.

[0051] A total weight of 7 grams of pure pre-melted sapphire cracked pieces was loaded into the inner crucible of the slow release container. A graphite growth crucible and lid similar to or corresponding to crucible 14 and lid 16 were made from halogen-purified dense isostatic graphite grade IG-11 available from Toyo Tanso USA Inc., 2575 NW Graham Cir, Troutdale, OR 97060. Prior to their use in crystal growth, the crucible and lid were halogen purified to an ash classification of less than 5 ppm by weight. The boron content in the purified graphite was determined to be 30 ppb by weight by impurity analysis using a glow discharge mass spectrometer (EAG LLC, 4747 Executive Drive, Suite 700, San Diego, CA 92121).

[0052] The doping container is loaded at the bottom of the graphite growth crucible, and a source crucible containing a SiC source corresponding to or similar to crucible 26 is loaded into the graphite growth crucible. The source crucible is placed on a support so that a free space is formed to accommodate the doping container. SiC seed crystals are attached to the lid of the graphite growth crucible and the graphite growth crucible is sealed with the lid. The SiC seed crystals are 4H-SiC and 6H-SiC wafers with a diameter of 150 mm. The 4H-SiC seed crystal is oriented with its growth surface facing the <000-1> crystallographic direction. The 6H-SiC seed crystal is oriented with its growth surface facing the <000-1> crystallographic direction. <0001> Orientation of the growth surface in the crystallographic direction.

[0053] The loaded graphite growth crucible was placed into a furnace chamber where it was surrounded by thermal insulation. The chamber was evacuated and the RF coil was powered to heat the graphite growth crucible to an initial temperature of 1400°C. At this temperature and under continuous pumping, the growth system was immersed for 24 hours to achieve the deepest possible degassing and reach 1·10 -6 The chamber was filled with UHP argon containing less than 10 ppb residual N2 to a pressure of 5 Torr, and a UHP argon flow of 300 sccm was established throughout the chamber.

[0054] The graphite growth crucible was then heated to a sublimation growth temperature. More specifically, the graphite growth crucible was heated to reach a temperature of 2180°C at the top of the crucible and a temperature of 2210°C at the bottom of the crucible. The top and bottom temperatures were measured and monitored with an optical pyrometer. The graphite growth crucible was immersed at the above temperatures for a predetermined period of time and then cooled to room temperature.

[0055] After the growth run is completed, the grown SiC crystal pears are recovered and fabricated into 150 mm diameter x 500 micron thick wafers according to SEMI standards. The wafers are first mechanically polished and then polished using a final CMP polish.

[0056] Example 2

[0057] The optical properties of the wafer produced in Example 1 were evaluated. The evaluation included measurement of its light transmission and reflection. Non-polarized light was measured in the wavelength range of 350nm to 850nm using a spectrophotometer (Agilent Cary 7000UMS). During the measurement of transmission, the angle of incidence (AOI) was 0°. During the measurement of reflection, the AOI was 6°. As outlined in Optical Processes in Semiconductors, JI Pankove, Dover Publ, NY, 1971, pages 93 to 94, the light absorption coefficient (α, cm) was calculated from the data on transmission and reflection using the approximation of a plate with parallel surfaces, thickness d and an infinite number of internal reflections. -1 ).

[0058] Wavelength dispersion (α, cm) of light absorption measured for some 4H-SiC wafers -1 )exist Figure 3 The wavelength dispersion (α, cm) of the light absorption measured for some 6H-SiC wafers is shown in -1 )exist Figure 4 Shown in. Figure 3 and Figure 4The curves of show the absorption coefficients in wafers doped with aluminum (lower curve) and wafers not doped with aluminum (upper curve). After the optical measurements, some of the measured wafers were cut into small pieces and the fragments were sent for N, B and Al impurity analysis by secondary ion mass spectrometry (SIMS) (EAG LLC, 4747 Executive Drive, Suite 700, San Diego, CA 92121). The results of the SIMS impurity analysis are shown in Table 2. Measures aimed at reducing background B and N contaminants include the use of halogen-purified graphite and extended hot zone vacuum baking, so that the levels of B and N in the grown SiC crystals are below 1·10 16 cm -3 The results of the light absorption coefficient measurements are also shown in Table 1. The SiC crystals in the last two rows of Table 1 were grown without deliberate aluminum doping and are shown in the table for comparison. The results obtained show that by aluminum doping, a greatly reduced light transmission in the visible spectral range is achieved.

[0059] Table 1

[0060]

[0061] This application also involves the following aspects:

[0062] 1. A composition comprising an aluminum-doped silicon carbide crystal having residual nitrogen and boron impurities, wherein the silicon carbide crystal comprises aluminum at a concentration greater than the combined concentration of nitrogen and boron in the silicon carbide crystal, and the silicon carbide crystal has a light absorption coefficient of less than about 0.4 cm at a wavelength in the range of about 400 nm to about 800 nm. -1 .

[0063] 2. The composition according to aspect 1, wherein the concentration of boron in the silicon carbide crystal is less than or equal to about 1·10 16 cm -3 .

[0064] 3. The composition according to aspect 1, wherein the concentration of nitrogen in the silicon carbide crystal is less than or equal to about 1·10 16 cm -3 .

[0065] 4. The composition according to aspect 1, wherein the concentration of aluminum in the silicon carbide crystal is less than about 5·10 17 cm -3 .

[0066] 5. The composition of aspect 1, wherein the silicon carbide crystals are substantially free of aluminum-induced defects.

[0067] 6. The composition according to aspect 1, wherein the silicon carbide crystals are 4H polytype or 6H polytype.

[0068] 7. The composition of aspect 1, wherein the silicon carbide crystals exhibit a wavelength of less than about 0.4 cm at a wavelength of about 450 nm. -1 The absorption coefficient.

[0069] 8. The composition of aspect 1, wherein the silicon carbide crystals exhibit a wavelength of less than about 0.05 cm -1 The absorption coefficient.

[0070] 9. The composition according to aspect 1, wherein the silicon carbide crystal exhibits a wavelength of less than about 0.01 cm -1 The absorption coefficient.

[0071] 10. A method for preparing aluminum-doped silicon carbide crystals, comprising:

[0072] providing a silicon carbide source material and a silicon carbide single crystal seed in a growth crucible;

[0073] providing a solid aluminum dopant source material comprising a compound containing aluminum and oxygen in a container; and

[0074] heating the growth crucible with the container positioned in the growth crucible in a manner effective to generate a silicon-and-carbon containing vapor from the silicon carbide source material in the growth crucible and an aluminum-containing vapor from the solid aluminum dopant source material in the container, and effective to deposit the silicon-and-carbon containing vapor and the aluminum-containing vapor on the silicon carbide single crystal seed to grow the aluminum-doped silicon carbide crystal,

[0075] Wherein the container comprises a first material resistant to damage by the aluminum dopant source and the aluminum-containing vapor, and a second material resistant to damage by the silicon- and carbon-containing vapor.

[0076] 11. The method of aspect 10, wherein the heating is also effective to produce solid aluminum oxide in the container and subsequently melt the solid aluminum oxide.

[0077] 12. The method of aspect 10, wherein the container comprises an inner component formed at least in part from the first material, and an outer component disposed about the inner component and formed at least in part from the second material.

[0078] 13. The method of aspect 10, wherein the container comprises a first layer formed at least in part from the first material, and a second layer formed at least in part from the second material.

[0079] 14. The method of aspect 10, wherein the first material comprises a refractory metal selected from tantalum, molybdenum, tungsten, rhenium, and alloys thereof.

[0080] 15. The method of aspect 10, wherein the second material is a refractory metal carbide.

[0081] 16. The method of aspect 15, wherein the refractory metal carbide is tantalum carbide or niobium carbide.

[0082] 17. The method of aspect 10, wherein the second material is graphite.

[0083] 18. The method of aspect 10, wherein the container further comprises a layer of refractory carbide.

[0084] 19. The method of aspect 10, wherein the container further comprises a capillary in gaseous communication with the aluminum dopant source material.

[0085] 20. The method of clause 10, wherein the aluminum dopant source material comprises aluminum oxide.

Claims

1. A physical vapor transport system, comprising: room; a growth crucible positioned in the chamber, the growth crucible being sealable with a growth crucible cover; as well as a doping vessel positioned in the growth crucible, the doping vessel comprising: an outer crucible equipped with an outer crucible cover; an inner crucible equipped with an inner crucible cover, the inner crucible equipped with the inner crucible cover being positioned within the outer crucible; and A capillary channel is formed by a first hole in the outer crucible cover and a second hole in the inner crucible cover.

2. The system of claim 1 further comprising a heating element positioned around the chamber.

3. The system of claim 2, wherein the heating element is a radio frequency (RF) coil or a resistive heating element.

4. The system of any one of claims 1 to 3, further comprising a source crucible housed within the growth crucible, the source crucible being separated from an interior bottom surface of the growth crucible by a support structure.

5. The system of claim 4, wherein the support structure comprises: a first member extending from an exterior lower surface of the source crucible to the interior bottom surface of the growth crucible; and a second member spaced apart from the first member, the second member extending from the exterior lower surface of the source crucible to the interior bottom surface of the growth crucible, wherein The first member, the second member, the outer lower surface of the source crucible, and the inner bottom surface of the growth crucible define a free space, the doping vessel being positioned within the free space, and The first member and the second member include holes for fluid communication between the space between the growth crucible and the source crucible and the free space.

6. The system of any one of claims 1 to 3, wherein at least the outer surface of the outer crucible and the outer surface of the outer crucible lid comprise graphite and / or refractory metal carbide.

7. The system of claim 6, wherein the refractory metal carbide is tantalum carbide or niobium carbide.

8. The system of any one of claims 1 to 3, wherein the outer crucible and the outer crucible cover are made of graphite.

9. The system of any one of claims 1 to 3, wherein at least an inner surface of the inner crucible and an inner surface of the inner crucible lid comprise a refractory metal or a refractory metal alloy.

10. The system of claim 9, wherein the refractory metal is tantalum, molybdenum, tungsten, or rhenium.

11. The system of claim 9, wherein the refractory metal alloy is an alloy comprising one or more of tantalum, molybdenum, tungsten, and rhenium.

12. The system of any one of claims 1 to 3, wherein the inner crucible and the inner crucible cover are made of tungsten.

13. The system of any one of claims 1 to 3, wherein an outer surface of the outer crucible cover and the outer crucible are at least partially formed of graphite and / or refractory metal carbide.

14. The system of claim 13, wherein the refractory metal carbide is tantalum carbide or niobium carbide.

15. The system of any one of claims 1 to 3, wherein the inner crucible and the inner crucible lid are at least partially formed of a refractory metal or a refractory metal alloy.

16. The system of claim 15, wherein the refractory metal is tantalum, molybdenum, tungsten, or rhenium.

17. The system of claim 15, wherein the refractory metal alloy is an alloy comprising one or more of tantalum, molybdenum, tungsten, and rhenium.

18. The system of any one of claims 1 to 3, wherein the capillary channel has a diameter ranging from about 0.1 mm to about 1.5 mm.

19. The system of any one of claims 1 to 3, wherein the growth crucible is at least partially surrounded by thermal insulation.

Citation Information

Patent Citations

  • System for forming SiC crystals having spatially uniform doping impurities

    US8216369B2